Demographic and Social Dimensions of the Neolithic Revolution in Southwest Colorado. Issue 3 (2nd July 2016) - Ortman, Scott G.; Diederichs, Shanna; Schleher, Kari; Fetterman, Jerry; Espinosa, Marcus; Sommer, Caitlin
Abstract : We address aspects of the Neolithic Revolution in the Mesa Verde region of Southwest Colorado. We first propose a new method of dating habitations within the Basketmaker III period (AD 600-725) using vessel forms in pottery assemblages. Then we adapt this method to new survey and excavation data to investigate demographic processes behind the formation of Mesa Verde Pueblo society. Finally, we quantify extramural storage space across Basketmaker III households to investigate the development of private property during this period. Our results indicate that both in-migration and intrinsic growth were involved in the formation of Mesa Verde Pueblo society; that agricultural households became increasingly dispersed over time; and that household agricultural outputs took the form of a log-normal distribution typical of societies with private property rights. Collectively, these findings suggest private property rights co-evolved with agriculture and settled communities, as researchers have suggested for other world areas.